Real-life analysis of neoadjuvant-therapy-associated benefits for pathological complete response and survival in early breast cancer patients - role of trastuzumab in HER2+ BC and platinum in TNBC - Chung, Wei-Pang; Yang, Chun-Ting; Yang, Shuen-Ru; Su, Ching-Yen; Su, Hsin-Wei; Liu, Shang-Yun; Ou, Huang-Tz (Frontiers in Oncology, 2023)
Background Neoadjuvant therapy, which aims to achieve a pathological complete response (pCR) for better overall survival (OS) has several advantages for patients with early breast cancer (eBC) and subtypes of HER2-positive (HER2+) and triple-negative breast cancer (TNBC). However, there has been no large-scale real-world investigation on the clinical outcomes associated with trastuzumab-based and platinum-based neoadjuvant treatments for patients with HER2+ and TNBC, respectively. Material and methods Taiwan Cancer Registry and National Health Insurance Research Database were utilized in this study. Patients diagnosed with clinically lymph-node-positive (LN+) HER2+ or TNBC were identified for analysis. Logistic regression and Cox proportional hazard models were employed to estimate the adjusted odds ratios (aOR) of achieving pCR and adjusted hazard ratios (aHR) of overall survival associated with treatment agents, respectively. Results A total of 1,178 HER2+ eBC and 354 early TNBC patients were identified, respectively. Neoadjuvant trastuzumab significantly increased the pCR rates by 3.87-fold among HER2+ patients. Trastuzumab-associated survival benefit was found in HER2+ patients who achieved pCR (aHR [95% CI]: 0.30 [0.11-0.84]) but not in those without pCR (1.13 [0.77-1.67]). Among the TNBC patients, platinum was associated with a 1.6-fold increased pCR rate; however, it did not improve OS regardless of pCR status. Conclusions Trastuzumab improved pCR and OS for patients with HER2+ subtype. Using platinum agents for TNBC patients increased pCR rates but was not linked to better survival. Optimal neoadjuvant anti-HER2 therapy for patients with HER2+ eBC and the introduction of novel therapy for patients with TNBC should be considered.